1997
DOI: 10.1073/pnas.94.3.884
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the mouse αA-crystallin gene induces cataract and cytoplasmic inclusion bodies containing the small heat shock protein αB-crystallin

Abstract: alpha A-crystallin (alpha A) and alpha B-crystallin (alpha B) are among the predominant proteins of the vertebrate eye lens. In vitro, the alpha-crystallins, which are isolated together as a high molecular mass aggregate, exhibit a number of properties, the most interesting of which is their ability to function as molecular chaperones for other proteins. Here we begin to examine the in vivo functions of alpha-crystallin by generating mice with a targeted disruption of the alpha A gene. Mice that are homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
242
2
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(262 citation statements)
references
References 31 publications
13
242
2
2
Order By: Relevance
“…1. We believe that some of these as yet undefined non-crystallin functions (38) of ␣A may be the reason for early cataracts in ␣A null mice (39). The observations made in this investigation may also explain why mutations in ␣A and ␣B have disparate phenotypic consequences (38).…”
Section: Discussionmentioning
confidence: 50%
“…1. We believe that some of these as yet undefined non-crystallin functions (38) of ␣A may be the reason for early cataracts in ␣A null mice (39). The observations made in this investigation may also explain why mutations in ␣A and ␣B have disparate phenotypic consequences (38).…”
Section: Discussionmentioning
confidence: 50%
“…Both proteins appear to have extensive nonlens roles (Nagineni and Bhat, 1992). Brady et al, (1997) showed that in αA crystallin knockout mice the lenses were smaller than wild type and developed opacification in the nucleus of the lens that became widespread with age. In the retina, studies on RPE from wild type and αA and αB knockout mice showed that both proteins were localized to the mitochondria and that a lack of alpha crystallins rendered RPE more susceptible to apoptosis following oxidative stress (Yaung et al, 2007).…”
Section: Mitochondrial Protective and Repair Systemsmentioning
confidence: 99%
“…αA and αB crystallin knockout mice (αA crystallin (−/−) and αB crystallin (−/−)) were originally generated at the National Eye Institute by targeted gene disruption and were maintained in the 129 S6/SvEvTac background (Brady et al, 1997;. The wild type mouse strain was also129 S6/SvEvTac (Taconic Farms, Germantown, NY).…”
Section: Intravitreal Injection To Micementioning
confidence: 99%